Муніципальна поліція як елемент правоохоронної системи деяких країн Європи - Голуб, М. В.; Holub, M. V.; ORSID: http://orsid. org/0000-0002-5257-081X (Південноукраїнський правничий часопис. - 2019. - № 4, ч. 2. - С. 26-29, 2019)
Визначено, що реформування системи органів МВС України спрямовується на вдосконалення та оптимізацію її структури, організацію діяльності з метою протидії злочинності, корупції, своєчасного виявлення та запобігання загрозам внутрішній безпеці України, підвищення рівня захисту прав і свобод громадян, профілактику злочинів і правопорушень. Наголошено, що для більш ефективного проведення заходів із забезпечення публічного порядку на території України було б доцільно розглянути можливість відновлення функціонування підрозділів муніципальної поліції, яка б сприяла регіональним поліцейськім підрозділам у вирішенні завдань щодо охорони публічного порядку та публічної безпеки. Запропоновано використати досвід роботи муніципальної поліції країн Європейського Союзу, а також і досвід України.

The article determines that the reform of the system of the Ministry of Internal Affairs of Ukraine is aimed at improving and optimizing its structure, organizing activities to counter crime, corruption, timely detection and prevention of threats to the internal security of Ukraine, increasing the level of protection of citizens’ rights and freedoms, prevention of crimes and offenses. The purpose of this process is the final transformation of the Ministry of Internal Affairs of Ukraine into a law enforcement agency that meets modern European requirements. It has been found out that the police of the German cities are in addition to the services which are responsible for the termination and prevention of offenses, there are units of municipal (communal) police, which control in the sphere of sanitation, trade, provision of services and so on. It is proved that in the Baltic States the municipal police acts as an element of the law enforcement system, which is entrusted with essential powers for the protection of public spinning at the local level, but we state that the municipal police in this country also acts as an auxiliary structure of the state police, and the employees are fulltime police officers. It is emphasized that the local police working in the city of Riga is an example of the activities of the municipal police (self-government police) of the Republic of Latvia. In 1995, the municipal police services of the city districts were merged into a single municipal police service of Riga. The police of Riga self-government has a complex and complex structure consisting of the headquarters, six district departments and four specialized departments for rendering services. It was concluded that in order to carry out public order measures more efficiently in Ukraine, it would be advisable to consider restoring the functioning of municipal police units, which would assist regional police units in solving public order and public safety tasks. In this case, it is appropriate to use the experience of the municipal police of the European Union countries discussed above, as well as the experience of Ukraine.

Определено, что реформирование системы органов МВД Украины направляется на усовершенствование и оптимизацию ее структуры, организацию деятельности с целью противодействия преступности, коррупции, своевременного выявления и предотвращения угроз внутренней безопасности Украины, повышения уровня защиты прав и свобод граждан, профилактики преступлений и правонарушений. Отмечено, что для более эффективного проведения мероприятий по обеспечению публичного порядка на территории Украины было бы целесообразно рассмотреть возможность возобновления функционирования подразделений муниципальной полиции, способствующей региональным полицейским подразделениям в решении задач по охране публичного порядка и публичной безопасности. Предложено использовать опыт работы муниципальной полиции стран Европейского Союза, а также опыт Украины.
Голуб, М. В. Муніципальна поліція як елемент правоохоронної системи деяких країн Європи / Голуб М. В. // Південноукраїнський правничий часопис. - 2019. - № 4, ч. 2. - С. 26-29. - DOI: https://doi.org/10.32850/sulj.2019.4.2.5.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; поліція; police; полиция; Україна. Ukraine. Украина; зарубіжний досвід; foreign experience; зарубежный опыт; країни Європи; countries of Europe; страны Европы; муніципальна поліція; municipal police; муниципальная полиция; профілактика правопорушень; crime prevention; профилактика правонарушений; охорона публічного порядку; protection public order; охрана публичного порядка; реформування; reformation; реформирование